The Influence of Work Discipline and Work Motivation on Employee Performance at Bank Syariah Indonesia Malang Suprapto - Firmansyah, Aprialdo (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study explores the influence of work discipline and motivation on employee performance at the Malang Suprapto Branch of Bank Syariah Indonesia (BSI). Understanding these factors is important for improving performance in Islamic banking institutions. Background Problems: Employee performance in banking organizations is closely linked to behavioral and motivational factors. This study focuses on identifying whether work discipline and motivation significantly affect employee performance, both individually and simultaneously. Research Methods: A quantitative approach was employed using a survey method. The research population consisted of all 30 employees at the Malang Suprapto Branch of BSI, with saturated sampling applied. Data were collected through structured Likert-scale questionnaires and analyzed using multiple linear regression techniques. Findings/Results: The results indicate that work discipline has a positive and significant effect on employee performance (p = 0.004), and motivation also shows a positive and significant effect (p = 0.001). Simultaneously, both variables significantly influence performance (p = 0.000). The coefficient of determination (R² = 0.659) indicates that 65.9% of performance variation is explained by discipline and motivation. Conclusion: The study concludes that strengthening work discipline and motivation is essential for enhancing employee performance in Islamic banking settings.